A autodefesa processual plena como direito fundamental do acusado - Pinheiro, Michel (2009)
The Brazilian criminal procedure, even fundamentally guided by decree dated 1941, is increasingly suffering important influence of principles enshrined in the Constitution of 1988. The interpretation of the Code of Criminal Procedure, under the lights of art. 5 of the Policy Letter, gave new version to the institute inspired by fascist Italy, making it arguably garantista in relation to fundamental rights directly linked to procedural content standards. Brazil ratified international human rights treaties, giving them legal force and demonstrating the will to be part of the universal network protection of human dignity. Two of the treaties contain rules that suggest greater involvement of the accused in criminal proceedings the evidence of the production: the Pact of San José, Costa Rica and the International Covenant on Civil and Political Rights. The criminal procedure self-defense is a subject that has been considered restrictively unanimously by the Brazilian doctrine and case law, recognizing the defendant only the right to be questioned directly by the judge and to be present to procedural acts. Recognize a legitimate right to self-defense expansion of the processed conforms to maximizing participation, characteristic of the democratic regime. The expanded self-defense is, in fact, increased the ius postulandi. In each stage of the process can be extended participation of the accused in the production of evidence, but without excluding the defender, since there is the recognition that the technical defense is essential, even if it can not guarantee a certain efficiency. The procedural defense thus becomes an essential condition of the dignity of all who respond to process. The purpose of this study is to address the self-defense as a fundamental guarantee of the defendant, where the restriction is improper when processed either part and is prevented. There is no constitutional or legal provision preventing self-defense. Thus, seal the participation of the defendant amounts to restrict freedom of expression, reducing his dignity by stifling their autonomy and self-determination capacity.